The potential use of centella asiatics as antihelicobacter pylori agent - Suppian, Rapeah (Pusat Pengajian Kesihatan, 2016)
Centella asiatica (C. asiatica) is a medicinal plant that traditionally used for the treatment of variety disorder, including infections, inflammation and immune system deficiencies. This study was carried out to investigate the effects of different parts of C. asiatica (roots, petioles, leaves) extracted using methanol and water on yield, active compounds, antibacterial activity against Helicobacter pylori (H. pylori) as well as inflammatory activity of the H. py/or/-infected macrophage. The highest yield of crude extract was obtained by the methanolic leaves extract (35.8%). Thin layer chromatography (TLC) analysis showed that, the two main compounds of C. asiatica', asiatic acid and asiaticoside were only detected in the methanolic extract of the plant parts with R, values 0.97 cm for asiatic acid and 0.44 for asiaticoside respectively. High Performance Liquid Chromatography (HPLC) analysis confirmed the presence of these compounds in the methanolic extracts of C. asiatica but not in the water extracts of the plant parts. The methanolic extract of the plant parts also exhibited good activity against H. pylori by inhibiting the growth of the bacteria either with Minimal Inhibitory Concentration (MIC), Minimal Bacteriocidal Concentration (MBC) or by disk diffusion assay. Among the plant parts, the methanolic leaves extract showed the highest inhibitory effect with inhibition zone ranging from 7 mm to 9 mm, and MIC and MBC at 5 mg/ml. The methanolic extracts of the plant parts also capable of increasing the inflammatory activity of H. pylori infected macrophage by stimulating higher phagocytic activity as well as the production of nitric oxide (NO). However, the extracts were significantly reduced the production of hydrogen peroxide (H2O2) in the infected cells. In conclusion, these findings suggested that the methanolic extracts of C. asiatica may have promising anti-H. pylori agent that can eliminate the bacteria directly or by modulating the innate defense mechanism of the host.